Emulsifying Properties of Lecithin Containing Different Fatty Acids Obtained by Immobilized Lecitase Ultra‐Catalyzed Reaction. (17th December 2013) - Gan, Lu‐Jing; Wang, Xiang‐Yu; Yang, Dan; Zhang, Hua; Shin, Jung‐Ah; Hong, Soon‐Taek; Park, Sang Hyun; Lee, Ki‐Teak
Abstract: Lecitase Ultra and 6 triacylglycerol lipases (lipases PS, M, AH, AY, R, and AK) were immobilized on Amberlite XAD 7HP and used to catalyze the acidolysis reaction between lecithin and capric acid (C10:0) for comparison. The highest molar incorporation value (51.0 mol%) was observed for the immobilized Lecitase Ultra. Further, immobilized Lecitase Ultra was selected for catalyzing acidolysis between lecithin and fatty acids with different chain lengths (C6:0, C8:0, C10:0, C12:0, and C14:0). After reaction, free fatty acids were removed by SPE and the resultant was called modified lecithin fraction 1 (MLF1). The highest molar incorporation value was obtained for C10:0 (51.0 mol%) at 45 °C with a mole ratio of 10/1 (C10:0/lecithin) for 72 h. After removal of lysophosphatidylcholine by solid‐phase extraction from MLF1, the resultant modified lecithin fraction 2 (MLF2) was used to prepare an oil‐in‐water emulsion. All emulsions prepared with MLF2 exhibited significantly higher emulsion stability (ES) values (16.2–17.7) and smaller particle sizes ( d 32 0.40–0.49 μm, d 43 0.75–1.01 μm) than the emulsion prepared with unmodified lecithin (ES 14.1, d 32 0.76 μm, d 43, 1.26 μm) ( P < 0.05). Furthermore, less clarification and droplet aggregation were observed in emulsions prepared with MLF2 than in lecithin‐based emulsions. Overall, the MLF2s showed better emulsifying properties than lecithin.